A Prospective Study of Obesity, Metabolic Health, and Cancer Mortality. Issue 1 (27th November 2017) - Akinyemiju, Tomi; Moore, Justin Xavier; Pisu, Maria; Judd, Suzanne E.; Goodman, Michael; Shikany, James M.; Howard, Virginia J.; Safford, Monika; Gilchrist, Susan C.
Abstract : Objective: This study examined whether metabolic health status is associated with risk of cancer mortality and whether this varies by body mass index (BMI) category. Methods: A prospective study of 22, 514 participants from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort was performed. Metabolically unhealthy status was defined as having three or more of the following: (1) elevated fasting glucose, (2) high triglycerides, (3) dyslipidemia, (4) hypertension, and (5) elevated waist circumference. Participants were categorized into normal weight (BMI 18.5‐24.9 kg/m 2 ), overweight (BMI 25.0‐29.9 kg/m 2 ), and obesity (BMI ≥ 30 kg/m 2 ) groups. Cox proportional hazards regression was performed to estimate hazards ratios (HRs) and 95% confidence intervals (CIs) for cancer mortality during follow‐up. Results: Among participants with normal weight, participants who were metabolically unhealthy had an increased risk of cancer mortality (HR: 1.65; 95% CI: 1.20‐2.26) compared with metabolically healthy participants. The overall mortality risk for participants who were metabolically unhealthy and had normal weight was stronger for obesity‐related cancers (HR: 2.40; 95% CI: 1.17‐4.91). Compared with participants with normal weight, those who were metabolically healthy and overweight were at a reduced risk of any cancer mortality (adjusted HR: 0.79; 95% CI: 0.63‐0.99). Conclusions: There was an increased risk of overall and obesity‐related cancer mortality among metabolically unhealthy participants with normal weight.